KAZI MAULIK AND KARAKALPAK LITERARY WRITING - Orinbaeva J. T. (Journals Park Publishing, 2025)
The article examines the life and work of Kazi Maulik Bekmukhamed uli, a great master of the word of Karakalpak literature of the late 19th and early 20th centuries.
Keywords: Ancient Turkic language, linguistics, epic, short story, definition and love songs, conversation, Arabic-Persian elements, Oriental classics.